Kra canal project and its influence on world maritime trade - Zuhdi, Achmad; Turan, Eda (SAGE PUBLICATIONS LTD, 2022)
Kra Canal that has been discussed since 1850's, is a significant issue for world maritime shipping players and members of the industry. The main aims of constructing the canal are to reduce the overcrowd of Malacca/Singapore Straits and prevent piracy attacks. Vessels sailing from Indian Ocean to South China Sea could reduce up to 700 nautical miles (NM) or 1300 km. Kra canal would take place in the southern part of Thailand, with 102 km of length, 400 m of width, and 25 m of depth. Songkhla and Satun, two provinces in South of Thailand, are the starting and ending points of this canal. In this study, information regarding Kra Canal has been presented and voyage estimation of some ships in alteration of marine fuel oil consumption and costs have been calculated. It is estimated that Kra Canal could reduce up to 2 days with constant speed of 13 knots, without considering the congestion in Malacca/Singapore Straits. It is also predicted that the construction of the canal will effect world maritime transportation line and economy around canal.
Keywords: Kra Canal; Malacca Strait; maritime transport; simulation; CONSUMPTION; Engineering